Hegemoni Ideologi dalam Novel Ketika Cinta Bertasbih Karya Habiburrahman el Shirazy (Kajian Hegemoni Gramsci) - Fajrul Falah (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
This research is background by the idea that novels are works that do not only highlight the aesthetic elements of language, but as a medium or means for authors to convey their mission and message. The novel is full of meaning, either clear or implied. Mission, motif, purpose of the author represented through the fictional characters he constructed. The purpose of the research is to reveal the form ideological hegemony in the novel Ketika Cinta Bertasbih (KCB) creation Habiburrahman el Shirazy. Research on novels KCB with the Gramsci hegemony approach the author’s knowledge is based search in online journals indexed doaj.org, in the last five years it has not been found. The research method used is descriptive qualitative.  The research approach used Gramsci hegemony. The results of the research show, central figure in a novel like Khairul Azzam dan Anna Althafunnisa able to  deal with life’s problems well (happines), because they believe and carry out ther ideology anda religious values. The main problem thet emerged from the two figures was like education, romance, and marriage. The process of hegemony that occurs between two figures and most of the other characters went will, so that able to dampen potential conflict between character.